Ethnomathematics Of Gesibu Blambangan Gate As Mathematics Learning Materials - Elok Rahmawati; Toto Bara Setiawan; Sunardi Sunardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Ethnomathematics is the study of the relationship between mathematics and culture that found in society. This research was conducted at the GESIBU Blambangan Banyuwangi gate. The purpose of this study was to describe ethnomatematics form at the Blambangan GESIBU Gate and arrange it into the research product in the form of ethnomatematic-based student worksheets (LKS). This research is a qualitative research with descriptive data analysis. There are three data collecting technique being used, those are observation, interview, and documentation The subject of this research were four people, namely cultural observers, archaeologists, builders, and carvers. The results showed that there were an ethnomatematics in the arrangement of shapes and sizes for each component of the gate from its roof, body, foot and the carving. The shape and size from each gate component contain ethnomatatics, such as two-dimensional figure, solid figure/geometry, geometric transformation (reflection, dilation, and rotation), and arithmetic sequence patterns